Safety and immunogenicity of the quadrivalent human papillomavirus vaccine in patients with juvenile dermatomyositis: a real-world multicentre study - Grein, Ingrid Herta Rotstein; Pinto, Natalia Balera Ferreira; Groot, Noortje; Martins, Camila Bertini; Lobo, Aline; Aikawa, Nadia Emi; Barbosa, Cassia; Terreri, Maria Teresa; Fraga, Aline Coelho Moreira da; Oliveira, Sheila Knupp Feitosa de; Sztajnbok, Flavio; Paim Marques, Luciana B.; et al. (Bmc, 2020)
Background: Concerns about the safety and efficacy of vaccines in patients with autoimmune diseases (AID) have led to contradictions and low vaccination coverage in this population, who are at a higher risk of infections, including by human papillomavirus (HPV). Although HPV vaccines have been recommended for immunocompromised patients, there is still a lack of data to support its use for AID patients, such as juvenile dermatomyositis (JDM) patients. The aim of this study was to assess the safety and immunogenicity of the quadrivalent HPV (qHPV) vaccine in a cohort of JDM patients. Methods: JDM patients aged from 9 to 20 years and healthy controls (HC) were enrolled to receive a 3-dose schedule of qHPV vaccine from March/2014 to March/2016. Study visits were performed before the first dose, 1 month after the second and third doses, and 6 months after the third dose. Participants completed a diary of possible adverse events for 14 days following each dose of vaccination (AEFV). Disease activity and current therapy were analyzed at each visit for JDM patients. In addition, serum samples from all participants were collected to test antibody concentrations against HPV16 and 18 at each visit. Participant recruitment was conducted in ten Brazilian centres. From 47 eligible JDM patients and 41 HC, 42 and 35, respectively, completed the 3-dose schedule of the vaccine, given that five JDM patients and two HC had received doses prior to their inclusion in the study. Results: The AEFVs presented by the participants were mild and in general did not differ between JDM and HC groups. No severe AEFVs were related to the vaccination. Disease activity was stable, or even improved during the follow-up. One month after the third dose of the vaccine the JDM group presented seropositivity of 100% for HPV16 and 97% for HPV18, similarly to the HC group, who presented 100% for both serotypes (p = 1.000). Six months after the third dose the seropositivity for the patient group was 94% for both HPV types. Conclusions: The HPV vaccination in this cohort of JDM patients was safe and immunogenic. Since the seropositivity against HPV16 and 18 was very high after the 3-dose schedule, this regimen should be recommended for JDM patients.
Keywords: Juvenile dermatomyositis; Quadrivalent HPV vaccine; Safety; Immunogenicity